Local Wisdom on Rituals and Beliefs Related to Caring Mental Health of Elderly People in Ponemuang Community at Ubon Ratchathani Province - บรรเทิงสุข หงษ์ (UBRU Journal for Public Health Research, 2017)
The purpose of this study Local Wisdom on Rituals and Beliefs Related to Caring Mental Health of Elderly People in Ponemuang Community at Ubon Ratchathani Province.The sample of population consisted of 10 knowledgeable elders, 5 traditional healers, 15 elderly who recieve traditional. Chosen by purposive sampling and snowball sampling. Data collection was undertakenduring October to November 2015 through in-depth interviews and observation. Data analysis was performed through content analysis. The results of study Local Wisdom on Rituals and Beliefs Related to Caring Mental Health of Elderly People in Ponemuang Community at Ubon Ratchathani Province best delated Believe about Cause problem Mental health relationship with Buddhist, Spiritualism, kwan (soul) and fortune (Daung cha ta) included. (1) Exorcism :Magic healer (Mor Song) Meditation find out a cause of illness for treatment (2) Thai blessing ceremony for patient for treatment because their believed if kwan with in body make to healthy not illness Magic healer (Mor Song) who make Thai blessing ceremony call to kwan (soul) come back in a body. (3) Thai blessing ceremony (kwan): Magic healer will be 3 day. (4) Renewal (Tor arr yu) make to the illnesses cured or mitigated there were several ceremonies Welcome back to the mound and pray Destiny (Soo kwan kong,Saud cha taa). (5) To exorcise fortunately that is not good and what evil can do to fend off elimination then make a person immune to evil things. (6) Fortunately ritual: believe that the ritual when the victim lost miserably next to their fate must have luck. (7) Watering mantra: Pour holy water believed to cleanse evil off from the mind and body and life 8.Treatment with the Magic healer (Mor Song): The ability to communicate with spirits that are believed to be important. To ask them to stamp spirits spiritualist. To tell the cause of illness. Concluded that even in today’s modern medical treatment, but it also blends folk medicine in the form of applying local wisdom to heal. So, should lead the way in the study results provide clear and applied together to reflect on the context of society and culture, as well as treatment.